Developing QR Code Interactive Multimedia Worksheets for Improving Students’ Learning - Hadismi, Sonia; Putri, Desy Hanisa; Purwanto, Andik (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
This research was conducted to obtain problems and potentials so that considerations are obtained to make alternative policies (product design). This study aims to determine the feasibility of interactive multimedia-assisted LKPD, improving student learning outcomes and student responses to the developed LKPD. The type of research conducted is the type of research and development (RnD) with the ADDIE model (analysis, design, development, implementation, and evaluation). The results of this research include, (1) LKPD assisted by interactive multimedia QR Code of 99.04% is considered very feasible (2) increasing student learning outcomes by using tests before (pretest) and after (posttest) with N-Gain results in the medium category of 0.40 (3) based on student responses to LKPD assisted by interactive multimedia QR Code getting a very good category with a percentage of 81.17%. Based on the results of this study, it can be concluded that the LKPD assisted by interactive multimedia QR Code is very feasible to use on momentum and impulse material. In addition, the use of media can improve student learning outcomes.